The Effect Of The Poe (Predict-Observe-Explain) Model On Learning Outcomes Of Junior High School Students - Eka Novita, Fenny; Arif, Khairil; R, Oktavia; F, Az-Zahra; Karma, Lewak (Alpatih Harapan Semesta, 2025)
This study investigates the effect of the Predict-Observe-Explain (POE) learning model on junior high school students’ science learning outcomes amid the suboptimal implementation of the independent curriculum, which remains teacher-centered and limits student engagement. Using a Quasi-Experimental Nonequivalent Control Group Design, the sample consisted of Grade VII students of SMP Negeri 26 Padang selected through purposive sampling. Class VII.1 received POE-based learning, while VII.2 experienced conventional instruction. Data were collected through pretest–posttest multiple-choice assessments, implementation observation sheets, and student response questionnaires. Descriptive and inferential analyses, including normality, homogeneity, and t-tests, revealed that t_count > t_table, indicating a significant effect of the POE model on students’ science learning outcomes regarding substances and their changes. Implications highlight the POE model’s potential to enhance conceptual understanding and student participation. Recommendations include integrating POE routinely into science instruction and training teachers to apply inquiry-based models effectively.